Neural-specific deletion of Htra2 causes cerebellar neurodegeneration and defective processing of mitochondrial OPA1. - Victoria L Patterson; Alfred J Zullo; Claire Koenig; Sean Stoessel; Hakryul Jo; Xinran Liu; Jinah Han; Murim Choi; Andrew T DeWan; Jean-Leon Thomas; Chia-Yi Kuan; Josephine Hoh (PLoS ONE, 2014)
HTRA2, a serine protease in the intermembrane space, has important functions in mitochondrial stress signaling while its abnormal activity may contribute to the development of Parkinson's disease. Mice with a missense or null mutation of Htra2 fail to thrive, suffer striatal neuronal loss, and a parkinsonian phenotype that leads to death at 30-40 days of age. While informative, these mouse models cannot separate neural contributions from systemic effects due to the complex phenotypes of HTRA2 deficiency. Hence, we developed mice carrying a Htra2-floxed allele to query the consequences of tissue-specific HTRA2 deficiency. We found that mice with neural-specific deletion of Htra2 exhibited atrophy of the thymus and spleen, cessation to gain weight past postnatal (P) day 18, neurological symptoms including ataxia and complete penetrance of premature death by P40. Histologically, increased apoptosis was detected in the cerebellum, and to a lesser degree in the striatum and the entorhinal cortex, from P25. Even earlier at P20, mitochondria in the cerebella already exhibited abnormal morphology, including swelling, vesiculation, and fragmentation of the cristae. Furthermore, the onset of these structural anomalies was accompanied by defective processing of OPA1, a key molecule for mitochondrial fusion and cristae remodeling, leading to depletion of the L-isoform. Together, these findings suggest that HTRA2 is essential for maintenance of the mitochondrial integrity in neurons. Without functional HTRA2, a lifespan as short as 40 days accumulates a large quantity of dysfunctional mitochondria that contributes to the demise of mutant mice.